Preparation and Immunological Evaluation of Organic Acid Salts of Levamisole - Feng, Xiaoling; Yang, Yi; Wang, Jianhua (Asian Journal of Chemistry, 2014)
Four kinds of organic acid salts of levamisole were prepared from levamisole hydrochloride and organic acids (L-ascorbic acid, tartaric acid, citric acid and ferulic acid) by solvent crystallization method, respectively. The salts were characterized by elemental analysis, UV-VIS, FTIR, ESI-MS, DSC-TGA, solubility in water, melting point, optical rotation and pH in water. The immunosuppressed mice models were established by intraperitoneal injection of cyclophosphamide to verify and compare the effects of levamisole hydrochloride and organic acid salts of levamisole on immune functions of immunosuppressed mice. The results showed while significantly increasing the contents of serum IgM and IgG and the immune organ indexes in cyclophosphamide-induced immunosuppressed mice, levamisole ferulate and levamisole tartrate presented higher increases in IgG contents and immune organ indexes than other salts did. Thus, it could be concluded that levamisole ferulate and levamisole tartrate were more effective on immune enhancement than other salts.